Short- and long-term effects in the school system of a research immersion experience for science educators: An example from ANDRILL (Antarctic Geological Drilling) - Cattadori, M.; Florindo, F.; Rack, F. (Geosphere, 2011)
Since its fi rst fi eld season (2006–2007), the ANDRILL (Antarctic Geological Drilling) program has implemented an innovative educational and public outreach (EPO) program known as ARISE (ANDRILL Research Immersion for Science Educators), which has actively involved a group of selected educators in every phase of the research, from participation in fi eld activities to discussion of the scientifi c results. This method of research immersion has led to an impressive list of achievements, including the development of quality outreach initiatives and diverse educational materials, the involvement of a large number of schools using these resources, the creation of an international network of strongly motivated polar geoscience educators, and the realization of new and un expected professional opportunities for educators. In Italy this program initiated a specifi c project (progettosmilla.it), in accordance with the objectives of the ARISE Program. Thanks to the use of both a wide range of instruments (online and material) and the network of personal relationships provided by teachers involved in the program, ARISE has resulted in many short-term accomplishments. The development of new partnerships with local and national institutions has led to a number of middle- and long-term processes, rarely seen in similar EPO projects, resulting in the attainment of other goals. Research immersion experiences promote close interactions between teachers and scientists, and provide the potential for accomplishing other long-term educational outcomes. The shared development of educational resources by scientists and educators through ARISE has created an opportunity to advance scientifi c education within schools and, through outreach, in the general populace. Published 1331-1339 1.8. Osservazioni di geofisica ambientale 2.2. Laboratorio di paleomagnetismo 3.8. Geofisica per l'ambiente JCR Journal reserved